The Influence of Organizational Culture and Work ethic on Employees' Performance at Mayangkara Group Company - Handoyo Mewahaini; Helena Sidharta (Universitas Ciputra Surabaya, 2022)
This research is to find out the influence of organizational culture and work ethic on employees’ performance at Mayangkara Group Company. The importance of conducting this research is that there is a visible cultural change that needs further research, especially in relation to employees’ performance. The choice of work ethic as another variable studied was due to the closeness of culture and work ethic in building organizational performance. The technique that is used in this research is using saturated sampling technique in which the entire population is to be research sample, that is, all 50 employees of Mayangkara Group Head Office. The choice of head office is because the organizational culture is more visible at the head office. This research uses quantitative research method and data analysis uses multiple linear regression analysis by using SPSS 25 statistical tool. The result of this research shows that organizational culture variable does not affect on employees’ performance of Mayangkara Group Company. While, work ethic affects positive significant on employees’ performance of Mayangkara Group Company. The organizational culture variable is using in accordance with the existing theory but is less precise in describing the company’s culture, therefore further research needs to be done using a different cultural approach. Work ethic on the other hand, shows a significant influence on performance, this shows the importance of work ethic in developing employees’performance which will affect organizational performance.